Research on Separation of Waste Lubricating Oil and its Friction Performance - Hou, Feifan; Yang, Duo (International Journal of Mechanical and Electrical Engineering, 2025)
After a period of use, automobiles require lubricant replacement to ensure engine reliability. However, the main components of waste oil(wo) remain unspoiled. Researching their regeneration is crucial for environmental protection and sustainable energy development. This study utilized isopropanol as a flocculant and zeolite as an adsorbent to recycle waste lubricants. A comparison of the tribological, rheological, and compositional properties of the regenerated oil (RO) with fresh oil (FO) revealed that the former exhibits shear thinning, enhancing its friction-reducing effect. The optimal load for the RO is 140N, where the friction coefficient is 0.8833, and wear volume is 21% lower than that of FO.